2003
DOI: 10.1016/s0014-5793(03)00508-8
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine exposure in Fas type I cells is mitochondria‐dependent

Abstract: Previous studies have demonstrated that Fas-triggered activation of e¡ector caspases and subsequent nuclear apoptosis either is mitochondria-independent (type I cells) or relies on mitochondrial ampli¢cation of the initial stimulus (type II cells). We show herein that Bcl-2 overexpression in a prototypic type I cell line (SKW6.4) promotes mitochondrial generation of ATP and blocks Fas-triggered plasma membrane externalization of phosphatidylserine (PS). Moreover, overexpression of Bcl-2 attenuates macrophage e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…Furthermore, PS externalization and clearance of apoptotic cells are mitochondria-dependent events, which are regulated by Bcl-2, and dissociated from other features of the apoptotic program. 124 This may explain the finding in the previous report that apoptotic cells induced by etoposide and staurosporine treatment were not efficiently ingested: unengulfed apoptotic cells were consistently present at all doses and time points, even when treated cells were mixed with healthy and untreated cells. 125 For any immunomodulatory anticancer treatment to be effective, it is necessary to reverse an immunosuppressive situation.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, PS externalization and clearance of apoptotic cells are mitochondria-dependent events, which are regulated by Bcl-2, and dissociated from other features of the apoptotic program. 124 This may explain the finding in the previous report that apoptotic cells induced by etoposide and staurosporine treatment were not efficiently ingested: unengulfed apoptotic cells were consistently present at all doses and time points, even when treated cells were mixed with healthy and untreated cells. 125 For any immunomodulatory anticancer treatment to be effective, it is necessary to reverse an immunosuppressive situation.…”
Section: Discussionmentioning
confidence: 60%
“…Phosphatidylserine (PS) exposure was determined by flow cytometric detection of the PS-binding protein annexin V using the annexin V-FITC apoptosis detection kit (Oncogene Research Products, Cambridge, MA), as described previously (Uthaisang et al, 2003). Cells were costained with propidium iodide (PI) prior to analysis on a FACScan (Becton Dickinson, San Jose, CA) equipped with a 488-nm argon laser.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear Fragmentation-Nuclear condensation/fragmentation of Hoechst 33342 (1 g/ml)-labeled cells was evaluated as described previously (22). Cells were scored using a fluorescence microscope (Nikon ECLIPSE TE 200, Tokyo, Japan) equipped with a digital Hamamatsu CCD camera (C4742-95-12NBR).…”
Section: Methodsmentioning
confidence: 99%
“…Reportedly, APLT is not a substrate for apoptosis-activated caspases suggesting that alternative mechanisms may be involved (20). In line with this, PS externalization can be divorced from the common caspase-initiated pathway of apoptosis (21,22). Connor and Schroit (23) demonstrated that reversible PS externalization can be induced by -SH reagents in non-apoptotic cells.…”
mentioning
confidence: 96%